Northwest history. Mining. Production. 1930-03-18 (1930)
Plan increase in production. - Future bright for mayo silver-lead district -- plot developments. - Further increases in production from its holding in the Mayo Silver-lead district, Yukon territory, Canada, are presaged by developments and construction contemplated by Treadwell Yukon, in which the Bunker Hill & Sullivan is heavily interested.